The effectiveness of advertisement by Petronas on conservation of Malaysian Culture / Noorlida Daud - Daud, Noorlida (2012)
The semiotic elements which exist from the social culture create different ways of thinking among races. This research aimed to analyze the extent of message of community service advertisement able to be delivered through advertisements by PETRO-AS across the semiotics of races; and its effectiveness in preserving the cultures in Malaysia. Eight community service advertisements of PETRO-AS in four categories were used in this study. Two adverts with the theme of Chinese culture, two with Indian culture, two with Malay culture and two universal advertisements. The study conducted was based on factorial design 4 x 3 (four categories of community service advertisements and three categories of races) and data analyzed were based on scores from cognitive response, effective response, understanding, thinking, productive, reflective thinking and selfengagement by race. The number of samples will be able to accommodate the design requirements 4 x 3 as each group watches all the selected community service advertisements by PETRO-AS.